Ritual Syncretism and Legal Validity: A Jurisprudential Analysis of the Fidyah Semyang Tradition in Bengkulu - Elkhairati Elkhairati; Laras Shesa; Yusefri Yusefri (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This study explores the practice of Fidyah Semyang, which is a local tradition of the people of Suka Datang Village, North Curup, Bengkulu which is carried out as a form of redemption for the obligation to pray from someone who has died. Fidyah is given in the form of gold, money, and fragrances through rituals full of spiritual symbolism. This study aims to understand how this tradition is practiced, as well as how it is positioned within the framework of normative Islamic law which generally does not allow the delegation of bodily worship such as prayer to others, either in the form of qadha or Fidyah. The method used is qualitative-descriptive with an ethnographic approach and case studies, through in-depth interviews, participatory observations, and literature review of contemporary Islamic jurisprudence and jurisprudence. The results of the study show that Fidyah Semyang is a form of religious syncretism that develops from the interaction between Islamic teachings and local customary value structures. Although the practice has a strong social and spiritual function, it faces challenges from Islamic scholars and legal thinkers who consider the tradition to be a form of ‘urf fāsid (corrupt customs), as it lacks a solid basis in nash shari'i and can distort the correct understanding of worship in Islam. In conclusion, Fidyah Semyang reflects on the dynamics between cultural religious expression and normative Islamic authority, and shows how local Muslim communities negotiate their religious identities within the framework of ancestral heritage customs and traditions